WINTER SPORTS: SITUATION AND PROGRESS COVERAGE BY JOURNAL “TEOIYA I PRAKTIKA FIZICHESKOY KULTURY” - Batsina, O.N.; Mokrushina, I.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the winter sports situation and progress trends in the Teoiya i Praktika Fizicheskoy Kultury coverage for the last decade. Methods and structure of the study. We made a content analysis of the winter sports coverage by the Teoiya i Praktika Fizicheskoy Kultury journal for the period of 2011 to 2021 that totaled 132 issues with 5,366 publications. Results and conclusion. We analyzed the key trends in the winter sports coverage by the Teoiya i Praktika Fizicheskoy Kultury for the last decade. It should be emphasized that the national winter sports have clearly deserved more attention from the research community for the period. The winter sports coverage variation profile showed a persistent growth with minor sags in 2012, 2017 and 2019. Most of the articles considered different winter sports training issues and elements, mostly the physiological, biomechanical and psychological ones. We found it traditional for the research community to prioritize the winter sports elite training topics. Regional winter sports were found underrepresented in the coverage for the period. As for the winter sports range in the publications, we were surprised to find no publications on skeleton and bobsled despite the fact that they are listed with the Olympic sports. We would recommend the national sports research community give a higher priority to the studies of winter sports to expand this share of the Teoiya i Praktika Fizicheskoy Kultury coverage later on since these sports are historically, traditionally and deservedly ranked with the strategic segment of the national sports industry.